Current Situation and Mental Health of Pregnant Women During the Prevention and Control of Novel Coronavirus Infection: A Cross-Sectional Study on the Investigation of Influencing Factors - Zhao J; Li Y; Guo M; Zhang G; Chen P (Dove Medical Press, 2024)
Jing Zhao,1 Yan Li,1 Miao Guo,1 Guijuan Zhang,2 Ping Chen1 1Department of Gynaecology and Obstetrics, the First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, Henan, People's Republic of China; 2Department of Gynaecology and Obstetrics, the Second Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of ChinaCorrespondence: Ping Chen, Department of Gynaecology and Obstetrics, the First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, Henan, People's Republic of China, Tel +8613783589566, Fax +86037166262974, Email pingping6768@126.comBackground: COVID-19 is a highly contagious respiratory infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which became a global public health crisis. In the past 3 years, the COVID-19 pandemic has resulted in a dramatic increase in the occurrence of psychological symptoms such as depression, anxiety, and stress in global populations. Therefore, it is important to help pregnant women cope with major public emergencies and improve their physical and mental health.Objective: To investigate the status and influencing factors of anxiety, insomnia, and psychological stress disorder in pregnant women with COVID-19 to provide a theoretical basis for psychological intervention in pregnant women in the case of public health emergency events.Patients and methods: A cross-sectional survey was conducted with 435 pregnant women from multiple tertiary hospitals in Zhengzhou from November 6 to December 6, 2022. The questionnaire contents included the general information of pregnant women, insomnia scale, generalized anxiety scale, and the revised version of the Accident Impact Scale.Results: There are 251 pregnant women with anxiety (57.7%, 95% CI: (53.0%-62.4%).There are 166 pregnant women with insomnia.(38.2%, 95% CI: 33.6%-42.7%), There are 314 pregnant women with stress disorder.(72.2%, 95% CI: 68.0%- 76.4%). During the epidemic prevention and control period, whether pregnant women had a history of adverse pregnancy had a statistically significant difference in anxiety, insomnia and stress disorders.Conclusion and Recommendation: During the COVID-19 pandemic, pregnant women appeared to generally have anxiety, insomnia, and stress disorders. Poor pregnancy history is a protective factor for pregnant women with anxiety, insomnia, and post-traumatic stress disorder. In the case of similar public health emergencies, attention bias modification (ABM) may be a potential intervention measure to provide potentially new ideas for alleviating the psychological disorders of pregnant women during this special period.Keywords: novel coronavirus infection, pregnancy, anxiety, insomnia, psychological stress disorder